THE CORRELATION BETWEEN INDONESIAN UNIVERSITY STUDENTS’ RECEPTIVE VOCABULARY KNOWLEDGE AND THEIR READING COMPREHENSION LEVEL - Dang Arif Hartono; Stefanus Angga Badara Prima (Indonesian Journal of Applied Linguistics)
While the literature has shown that vocabulary mastery affects reading comprehension, only a few Indonesian researchers investigated this. To narrow this gap, this study aims to: 1) measure Indonesian university students' knowledge of receptive vocabulary, 2) measure their reading comprehension level, and 3) investigate the association between the two variables. The participants in this study were 168 first-year university students from a private university implementing English-medium instruction (EMI). We utilized the updated vocabulary level test to measure their receptive vocabulary size and the IELTS academic reading test to measure their reading comprehension level. The participants mean scores on the updated VLT were 28.73, 26.63, 22.27, 22.42 and 23.12 at the 1,000, 2,000, 3,000, 4,000, and 5,000-word level respectively. Only 34 out of 168 participants could be considered to have a sufficient vocabulary size. On average they scored 16.08 (SD = 7.96) on the IELTS academic reading test, which was roughly equivalent to 5 in IELTS band score. We also found strong and significant correlations between the participants’ scores on the IELTS academic reading test and the updated VLT at all levels, with the largest effect size on the 4,000-word level (r = .71, p .001, BCa 95% CI [0.64, 0.78], r2 = .50). These findings indicated that the participants did not have sufficient vocabulary knowledge and had a low reading proficiency, potentially inhibiting progress in their academic pursuits. We discussed the findings in relation to the teaching of English in EFL, ESL, and EMI contexts. Practical implications of the findings are also discussed.